Comparison of below knee cast and elasticated support bandage treatment foe an isolated fracture of the lateral malleolus - Maharjan, Rajram (Journal of Society of Surgeons of Nepal, 2017)
Introduction: Ankle fractures are the most common type of fractures treated in orthopaedics with isolated malleolar fractures, accounting for two-thirds of fractures. The most common injury mechanism is supination external rotation, which accounts for the majority of all ankle fracture patterns. Supination external rotation stage II is the classic short oblique fracture of the distal fibula without a medial side injury, which responds well to non-operative treatment as it is a stable fracture. The purpose of this study is to compare efficacy of elasticated support bandage versus plaster cast in the patient with isolated lateral malleolus fracture (Lauge-Hansen supination- eversion external stage II.)Method: A prospective comparative study was carried out in the Department of Orthopaedics in Bir Hospital from February 2007 to January 2009. Patients with ankle fracture were initially treated by below knee posterior slab for seven days to allow the swelling to subside and on seventh day follow-up they were grouped in two groups. Group A were patients with below knee cast and Group B were elasticated support bandage. Both groups were followed-up in the 5th week for cast or elasticated bandage removal and were evaluated after a week, thereafter, every monthly for 3 months and finally at 6 month.Result: Of the 48 cases enrolled, the mean age of the patients was 38.85 years. The common mode of injury was fall from height followed by road traffic accident. The modified subjective ankle score of Olerud and Molander (1984) was found more in group B in comparison to group A in all follow ups. In initial three successive follow ups at 6 week, 12 week and at 3 month subjective score was found statistically significant (p> 0.05) however, it was not significant at 6 month follow up. The range of motion was significantly improved in group B in all follow ups but the difference between the two groups at 6 weeks and 10 weeks follow ups was statistically significant. Immobilized group required less analgesic but the difference was not significant statistically.Conclusion: Both below knee cast and elasticated support bandage treatment methods are safe, satisfactory and equally effective with a better early result in elasticated support bandage. Supination External Rotation stage II type fracture can be treated conservatively, if there is no medial tenderness.Journal of Society of Surgeons of NepalVol. 17, No. 2, 2014, Page: 7-11